Some exact solutions to the potential Kadomtsev-Petviashvili equation and to a system of shallow water wave equations - Inan, IE; Kaya, D (Elsevier Science Bv, 2006)
In this Letter by considering an improved tanh function method, we found some exact solutions of the potential Kadomtsev-Petviashvili equation. Some exact solutions of the system of the shallow water wave equation were also found. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: potential Kadomtsev-Petviashvili equation; improved tanh function method; traveling wave solutions; system of the shallow water wave equation